The Influence of Organisation Dimension in Business Analytics Adoption by Malaysian SMEs - Atan, Mislina; Mahmood, R. (Journal of Advanced Computing Technology and Application (JACTA), 2022)
The use of various technologies by business organisations produces data, which later be converted into meaningful insight through the business analytics process. Prior studies based on the DOI, TOE framework, and Dynamic Capability Theory reported that top management support and organisational readiness were the main attributes that influence technology adoption. However, there were inconsistent findings and required further investigation. Thus, this study examines the relationship between top management support and organisational readiness in business analytics adoption. This deductive study used an online survey questionnaire for data collection. The sample was selected using systematic random sampling from a national directory of Malaysian entrepreneurs. The finding based on 241 data showed that top management support and organisational readiness influence business analytics adoption in Malaysian SMEs. Managers, owners, vendors, and policymakers can use these findings to facilitate and spur the adoption of business analytics.